Hubungan Dividen Inisiasi dan Informasi Asimetri: Pendekatan Hazard Rate - Hadri Kusuma (Management Development Centre (MDC) Department of Management, Faculty of Business and Economics Universitas Islam Indonesia, 2004)
This research examines the dynamics of dividend policy applying the hazard model. The study focuses on the dividend initiation for a sample of firms went public on the Jakarta Stock Exchange between 1990 and 1997. These dividend initiations are investigated in the contect of pecking order theory. The results of the tests indicate that the hazard rate of a dividend initiation is negatively related to both level of asymmetric information and growth, but positively related to the level of agency costs. The results are consitent with the theory of pecking order but do not provide a support for a signaling theory.